Strategi Pembelajaran Bahasa Inggris di Sekolah Dasar: Studi Systematic Literature Review - Nafiatu, Sofia; Mulyani, Petra Kristi (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
This study aims to review the literature related to English learning strategies used in elementary schools (SD). This research method uses the SLR (Systematic Literature Review) method. Data collection was obtained by selecting previous research articles related to the theme of elementary school English learning strategies from the Google Schoolar database from 200 articles obtained from initial data collection, 7 articles were selected after a screening process using inclusion and exclusion criteria. The results of this study contain 7 strategies, namely Game Based Learning (GBL), English grammar teaching for elementary schools is very necessary, Methods that can be provided by teachers are Grammar Translation Method (GTM), Audio Lingual Method and Total Physical Response, For reading skills teachers can use the Dialogic Reading strategy, The next strategy is that teachers must be able to touch the language needs of students by adjusting the conditions and daily situations of students, Teachers can develop realia media to teach English, Teachers can use Enjoyable Learning strategies assisted by audio visual media to improve English learning outcomes in elementary schools.